Effectiveness of Spatial Management of the One-Stop Integrated Service Section at the Makassar State Administrative Court - Sitti Hardiyanti Arhas; Achmad Khatami; Muhammad Zulfikar; Andi Octamaya Tenri Awaru (Jurnal Office, 2022)
Office layout is the art of arranging a room in order to produce a comfortable working climate and ultimately to create productivity and work efficiency. The purpose of this study was to determine the effectiveness of the office layout of the one-stop integrated service division at the Makassar State Administrative Court. To determine the purpose of the study, a qualitative descriptive research was used. There were 6 informants in this study using data collection techniques through observation, interviews, and documentation. The data obtained from the research results are then processed using data analysis techniques consisting of data reduction, data presentation, and drawing conclusions. The results showed that the arrangement of the one-stop integrated service space at the Makassar State Administrative Court was good for the shortest distance, work sequences, and changes in the arrangement of the workplace, and for the use of all the rooms it was considered quite good but not optimal.